Calibration of bonded-particle model parameters and simulation of compression behavior for oilseed rape shoot stalks - Shan, Yiyin; Liao, Qingxi; Wan, Xingyu; Yuan, Jiacheng; Liao, Yitao; Gao, Daxin (International Journal of Agricultural and Biological Engineering, 2024)
The relationship between the parameters of the bonded-particle model and the macroscopic properties of oilseed rapeshoot stalk provides valuable insights into the interaction between the stalks and harvesting machinery. In this study, a discrete element model of oilseed rape shoot stalk was constructed using a method that combined ordered and bimodal distribution filling. The model’s six contact and five bonding parameters were calibrated based on physical and simulated diametral compression tests. The Plackett-Burman design was employed to screen the effects of the parameters on the rupture force. Therange of significant parameters was determined using the steepest ascent test. Furthermore, by calculating the second-order regression model and analyzing the significance of parameter combination using the central composite design method, the optimal parameter combination was identified, including a bonded disk radius of 0.78 mm, a normal stiffness per unit area of 4.61×107 Pa, a shear stiffness per unit area of 5.21×107 Pa, and a coefficient of static friction between particles of oilseed rapeshoot stalk of 0.47. The simulated rupture force (58.80 N) differed by 6.5% from the average value of the physical test (62.92 N), and the deformation of the compression process was consistent. The results demonstrate that the model effectively reflects he mechanical failure properties of oilseed rape shoot stalk during the diametral compression, providing a reference for modeling other crop stalks and aiding in the study of interactions between clamping-transporting devices and stalks duringharvesting.Keywords: oilseed rape shoot, discrete element model, ordered and bimodal distribution filling method, mechanical properties, parameter calibrationDOI: 10.25165/j.ijabe.20241706.8833Citation: Shan Y Y, Liao Q X, Wan X Y, Yuan J C, Liao Y T, Gao D X. Calibration of bonded-particle model parameters and simulation of compression behavior for oilseed rape shoot stalks. Int J Agric & Biol Eng, 2024; 17(6): 46–58.